Evaluation Of Planning And Implementation Occupational Safety And Health In Hospital Embung Fatimah Batam In 2021 - Noni Rokaya Pasaribu; Ermi Girsang; Sri Lestari Ramadhani Nasution; Chrismis Novalinda Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
Hospital occupational health programs have not been fully implemented in hospitals such as evaluation of the work environment, documentation of special and periodic health checks, the risk of occupational diseases (PAK). This type of research is qualitative with 10 informants selected purposively. on the input component: HR K3, the budget, and safety facilities provided are still lacking. In the process component: Risk management, hospital safety and security efforts, occupational health services, and B3 management are good. There are not enough fire prevention and control facilities. Infrastructure management is good with water sources, backup electricity, and periodic maintenance. Management of medical equipment and disaster preparedness is good. In the output component: Supervision is carried out by internal hospitals cases of work accidents are still found, and there is still a shortage of human resources, budget, and K3 facilities. It is recommended to the management of the hospital to add human resources in the field of work safety according to standard.